The Destruction of Prophet Saleh's People in the Qur'an (Tafsir Study of Ibn Kathir) - Nabila Tushadiah Pratiwi; Siti Masykuroh; Beko Hendro (ZAD Al-Mufassirin, 2025)
The aim of this research was to analyze the meaning of the story thematically and to identify its relevance for contemporary society. This study employed the thematic interpretation method ( tafsir maudhu'i ) with a library research approach, focusing on three main chapters: QS. Al- A'raf : 73–79, QS. An-Naml: 45–53, and QS. Al-Qamar: 23–32. The findings revealed that from a socio-historical perspective, the material advancement of the Thamud civilization was not accompanied by moral maturity, leading to greed, social injustice, and environmental exploitation. From a phenomenological perspective, their rejection was understood as a form of closed consciousness, arrogance, and spiritual alienation from monotheism. Ibn Kathir's commentary strengthens this analysis by providing detailed reports and chronology that confirms the pattern of destruction among nations that rejects the truth. The novelty of this study lay in synthesizing classical exegesis with thematic and multidisciplinary approaches to provide a more comprehensive understanding. Its implications are relevant to contemporary issues such as environmental degradation, social inequality, and the reinforcement of transcendental values as the foundation of moral and social policies.